Positive effects of antihypertensive treatment on aortic stiffness in the general population - Seidlerová, Jitka; Filipovský, Jan; Mayer, Otto; Wohlfahrt, Peter; Cífková, Renata (Hypertension research, 2014)
Aortic stiffness is strongly related to age and mean arterial pressure (MAP). In the present analysis, we investigated whether antihypertensive treatment modulates the association of the aortic pulse wave velocity (PWV) with age and with MAP in the general population. In the Czech post-MONICA cross-sectional study, we measured the PWV in 735 subjects (mean age 61.2±7.8 years, 54.1% women, 44.3% on antihypertensive medication). We used a linear regression model to assess the effect of treatment on the PWV. The independent covariates in our analysis included sex, age, MAP, heart rate, body mass index, plasma glucose, low-density lipoprotein cholesterol, smoking and observer. The patients receiving treatment were older (64.1±6.7 vs. 58.9±7.8 years), had higher systolic blood pressure (135.9±16.2 vs. 130.1±16.5 mm Hg) and had higher pulse wave velocity (9.1±2.2 vs. 8.2±2.1 m s(-1); P for all <0.0001) than untreated subjects. After adjustment for MAP, the use of treatment modified the association between age and the PWV (regression equations, treated patients 9.68-0.009 × age vs. untreated subjects 6.98+0.020 × age, difference of regression slopes, F=11.2; P=0.0009). In analyses adjusted for age, treatment was associated with a smaller increase of the PWV with MAP (treated patients 9.63-0.006 × MAP vs. untreated subjects 7.18+0.010 × MAP, F=10.70; P=0.0001). These results were driven primarily by subjects whose blood pressure was below 140/90 mm Hg. In the cross-sectional analysis from a random sample of the general population, antihypertensive treatment was associated with a less steep increase in the PWV with age and the mean arterial pressure. Further longitudinal studies are needed to confirm this finding.
Keywords: dospělí; hypertenze; průzkumy a dotazníky; Female; Pulse Wave Analysis; Models, Statistical; Adult; ženské pohlaví; průřezové studie; Surveys and Questionnaires; Aging; aorta; lidé; analýza pulzové vlny; statistické modely; tuhost cévní stěny; Cross-Sectional Studies; Hypertension; Male; Aged; stárnutí; lidé středního věku; Antihypertensive Agents; Aorta; senioři; mužské pohlaví; antihypertenziva; Vascular Stiffness; Middle Aged; Humans